PERSEPSI PLAYER TERHADAP POTENSI EKONOMI GAME MOBILE LEGEND SURVEI PADA MAHASISWA UIN FAKULTAS EKONOMI DAN BISNIS ISLAM - M. Adliansyah; A.A. Miftah; Muhammad Subhan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine Player Perceptions of the Economic Potential of the Mobile Legend Game (Survey of UIN Students, Faculty of Islamic Economics and Business). The number of informants in this research was 10 informants, namely students from the Islamic Economics and Business Faculty. This type of research is descriptive qualitative with primary data and secondary data. The data collection technique in this research uses observation, documentation and interview techniques, while for data analysis the researcher uses editing (data presentation), clarification and description. The results of this research explain students' perceptions about the economic potential and new professions in the field of online games, especially mobile legend games